MULTILINGUALISM AND LANGUAGE CONTACT IN THE POETIC WORLD OF ALEXANDER FAYNBERG - Abdumalikova Sevinch Tayirovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article explores the phenomena of multilingualism and language contact within the poetic corpus of Alexander Faynberg. As a prominent Russian- speaking poet of Uzbekistan, Faynberg’s work serves as a unique linguistic intersection where Slavic syntactical structures meet Turkic cultural and conceptual frameworks. The study employs a contact-linguistic approach to analyze the integration of Uzbek loanwords, cultural realia, and "conceptual calques" into his Russian verses. Beyond mere lexical borrowing, the research investigates how this multilingual environment shapes the poet’s metaphorical system and stylistic identity. The findings suggest that Faynberg’s "bilingual consciousness" creates a hybrid poetic space that facilitates intercultural dialogue and reflects the complex sociolinguistic landscape of 20th- century Central Asia. This study contributes to the field of transcultural linguistics by demonstrating how language contact can enrich poetic expression and foster a unified "National-Universal" aesthetic.